Targeting dynamics of Thermococcus kodakarensis RNA methyltransferases - Elkins, Liam, author; Santangelo, Thomas, advisor; Schauer, Grant, committee member; Wilusz, Jeffrey, committee member (Colorado State University. Libraries, 2025)
Site-specific RNA modifications are abundant across all domains of life, installed by a suite of RNA modification enzymes that generate the bulk of the epitranscriptome by selectively targeting RNAs for modification. Thermococcus kodakarensis is an archaeal species that thrives at extreme temperatures and generates a densely modified epitranscriptome, making it an ideal model organism for studying mRNA modifications—specifically, 5-methylcytosine (m5C). The RNA motifs or structures targeted for site-specific modifications installed by RNA methyltransferase enzymes are largely undefined, prohibiting efforts to selective modify RNAs through the addition of a minimal targeting sequence(s). Here we first establish the necessary and sufficient RNA motifs for site-specific modification in vitro, then demonstrate that appending these minimal RNA motifs to non-targeted mRNAs in vivo suffices to direct site-specific modifications on "chimeric" mRNA targets. Several RNA methyltransferase – RNA motif pairs have been established to generate an efficient, highly selective, and customizable RNA-modifying system . Our combined results open a new platform for directed RNA modification using optimized RNA methyltransferase – RNA motif pairs.
Keywords: enzyme; RNA; methytransferase; archaea